Fintech and its challenge for banking sector - diyan lestari; Basuki Toto Rahmanto (STIE Binaniaga, 2021)
Abstract: The rapid development of technology has shifted consumer behavior which impact on business, including banking sector. It is expected that technology can be optimized to improve productivity and performance. In banking sector, technology plays important role to ease the financial transaction and minimize cost. In the digital age, most of individual activities are conducted by technology, including completing their financial transaction. Technology also helps to promote financial inclusion. Furthermore, the Covid-19 pandemic has leveraged the digital adoption into different level due to the social distancing practice. This study aims to investigate the fintech strategy to enter the financial service sector, and how bank response the fintech development. This study is a qualitative research which implemented depth interviews and content analysis. Moreover, this paper utilized both primary and secondary data in order to provide valid investigation. This study found that fintech is basically innovative, and promotes innovative strategy to enter the financial service industry, while banks have already prepared to compete in the digital age. Several strategies were formulated by banks to win the competition, including investing in software, hardware, and even in financial technology companies. Kata kunci: fintech, banking, innovation